Spatial variation in pollinator communities and reproductive performance of Prosopis juliflora (Fabaceae) - Asif Sajjad (Journal of Pollination Ecology, 2012)
This study was conducted in an effort to understand the effects of spatial variations in pollinator assemblage due to habitat isolation on the reproductive performance of perennial plant species. Variations in pollinator assemblage structure (abundance, diversity and Shannon-Wiener index) were studied at three widely isolated (100 to 200 km apart) nature reserves of Southern Punjab, Pakistan, in order to explore its effects on reproductive performance of Prosopis juliflora. Species richness and abundance were highest in Pirowal Sanctuary followed by Chichawatni Sanctuary and Chak Katora forest reserve. The pollination system of P. juliflora was highly generalized with 77 insect visitor species in four orders among all the three sites. However, pollinator assemblage varied significantly in composition among the sites. Out of the four reproductive parameters considered, the number of pods per raceme and germination varied significantly among the three locations. The reproductive performance of P. juliflora in terms of number of pods per raceme and germination improved with abundance of pollinators.